TEACHER PROFESSIONAL DEVELOPMENT AND INSTRUCTIONAL INNOVATION IN REMOTE CONTEXTS: TEACHERS' PERCEPTIONS OF GASING IMPLEMENTATION IN PAPUA - Istia, Maryo Sopater; Likumahwa, Fervin Mayos; Luas, Alfando; Sawaki, Yusuf; Bien, Masri Yomima (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Teacher professional development is widely recognized as a key driver of instructional innovation, particularly in geographically remote and under-resourced educational settings. However, limited evidence is available regarding how teachers perceive instructional innovations following professional development experiences in such contexts. This study aimed to examine teachers’ perceptions of the GASING (Gampang, Asyik, dan Menyenangkan) method and explore the relationships among key perception dimensions associated with instructional innovation in a remote educational setting. A quantitative descriptive design was employed involving 22 elementary and junior high school teachers in Teluk Bintuni, West Papua, Indonesia, who had participated in GASING training. Data were collected using a structured questionnaire covering six dimensions: cognitive understanding, affective response, pragmatic value, contextual feasibility, interest and engagement, and behavioral intention. Descriptive statistics and Chi-square tests were used for data analysis. The results revealed consistently positive perceptions across all dimensions, with mean scores ranging from 4.00 to 4.77 on a five-point scale. Teachers demonstrated strong cognitive understanding, positive affective responses, and high perceived practical value of the GASING method. Chi-square analysis showed that most dimensions were statistically independent, although a marginal association was found between contextual feasibility and behavioral intention (χ² = 3.009; p = 0.083). These findings suggest that positive teacher perceptions alone may not ensure sustained instructional change in remote contexts.